Implementation of Floating Net Cages (FNC) cultivation and risks to sustainable fisheries in the Gajah Mungkur Reservoir, Wonogiri, Central Java, Indonesia - SANTI KURNIASIH; SUNARTO SUNARTO; PRABANG SETIAWAN (Smujo International, 2024)
Abstract. Kurniasih S, Sunarto, Setyono P. 2024. Implementation of Floating Net Cages (FNC) cultivation and risks to sustainable fisheries in the Gajah Mungkur Reservoir, Wonogiri, Central Java, Indonesia. Nusantara Bioscience 16: 228-236. Floating Net Cages (FNC) is an effort to intensify fish production in the Gajah Mungkur Reservoir, Wonogiri, Central Java, Indonesia. The increase in the number of FNC is directly proportional to the production of FNC fish, so it can decrease water quality. The study aims to look into how FNC affects the water quality in the FNC area of the Gajah Mungkur Reservoir and how the threat of FNC water conditions affects the long-term viability of FNC aquaculture in the Gajah Mungkur Reservoir. The data collection technique was purposive sampling, which was analyzed using quality standard evaluation and plankton community structure analysis. The research results show that the water quality parameters measured are based on standards for fisheries activities, except for the COD and BOD parameters. Most plankton found are from the Bacillariophyceae class. The FNC area in the Gajah Mungkur Reservoir includes eutrophic waters with a low diversity and moderate pollution. The evenness exceeds 6 and the C value is less than 0.5. The saprobic indexes for the pollution level in the FNC area’s waters is classified as very low to low, with few organic and inorganic compounds in the Oligo/?-Mesosaprobik to ?-mesosaprobik phase. Six families of fish have been found in the Gajah Mungkur Reservoir, namely Cyprinidae, Pangasiidae, Eleotrididae, Cichlidae, Channidae, and Bagridae. Social conflict, mass fish deaths, and increasing water pollution are risks to floating net cages cultivation. Commitment, implementation, and supervision are crucial in executing FNC management through an ecosystem approach, ensuring the sustainability of FNC aquaculture and preserving food security.